Алгебра
Алгебра, 21.10.2019 00:02, UncrownedKing

Вопрос/Задача:

(x^2-7x+6)(x^2-2x-4)=0 с уравнением,

Ответы на вопрос

Ответ
Ответ разместил: Гость

переведем дроби в неправильные. получаем

√ (25/14) * √ (7/2) = √ ((25 * 7) / (14 * 2)) = √ (175 / 28) = √ (25 / 4) = 5 / 2 = 2,5

 

Ответ
Ответ разместил: Гость

4b+2m/2(4b+3m)-3b+2m/2(4b+3m)=(4b++2m)/2(4b+3m)=4b+2m-3b-2m/2(4b+3m)= b/2(4b+3m)

Ответ
Ответ разместил: Гость

b1 = b2/q = -6

ответ: -6

Ответ
Ответ разместил: Мэй15
(x^2-7x+6)(x^2-2x-4)=0 1)(x^2-7x+6)=0        2)(x^2-2x-4)=0 1)d=49-24=25 x1=3,5 x2=-1,5 2)  d=4+16=20 х3=1-√5 х4=1+√5

Похожие вопросы

Вопросов на сайте: